2008
DOI: 10.1017/s1473550408004175
|View full text |Cite
|
Sign up to set email alerts
|

The case for life on Mars

Abstract: There have been several attempts to answer the question of whether there is, or has ever been, life on Mars. The boldest attempt was the only ever life detection experiment conducted on another planet: the Viking mission. The mission was a great success, but it failed to provide a clear answer to the question of life on Mars. More than 30 years after the Viking mission our understanding of the history and evolution of Mars has increased vastly to reveal a wetter Martian past and the occurrence of diverse envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 205 publications
(301 reference statements)
0
24
0
Order By: Relevance
“…Spanish researchers at the Madrid Astrobiology Center, and later American groups, put forward the proposal that the strange spherules on Meridiani Planum could be related to a community of chemolithoautotrophic bacteria still living on Earth in acid environments enriched by iron minerals (Parro et al 2005;Jepsen et al 2007). Recently, other authors have found further evidence of life on Mars by detection of methane and formaldehyde (Onstott et al 2006 ;Schulze-Makuch et al 2008). The biological theory was also supported by Italian researchers (Caiola & Billi 2007); they supposed that some terrestrial organisms, from the cyanobacteria group and similar to the genus Chroococcidiopsis, could be adapted to Martian conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Spanish researchers at the Madrid Astrobiology Center, and later American groups, put forward the proposal that the strange spherules on Meridiani Planum could be related to a community of chemolithoautotrophic bacteria still living on Earth in acid environments enriched by iron minerals (Parro et al 2005;Jepsen et al 2007). Recently, other authors have found further evidence of life on Mars by detection of methane and formaldehyde (Onstott et al 2006 ;Schulze-Makuch et al 2008). The biological theory was also supported by Italian researchers (Caiola & Billi 2007); they supposed that some terrestrial organisms, from the cyanobacteria group and similar to the genus Chroococcidiopsis, could be adapted to Martian conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The electron donor H 2 could easily be generated by photochemical dissociation of water [66] and it has already been determined that there are large amounts of sulfate, especially in the form of MgSO 4 and FeSO 4 in the Martian soils [17,67].…”
Section: Conservation Of Energymentioning
confidence: 99%
“…Extrapolating our knowledge of terrestrial biotic sources to Mars, many consider methanogens (a type of Archaean microbe) as a probable analog to Martian life forms [22][23][24]. Some methanogens are able to utilize inorganic compounds (H 2 and CO 2 ) as their only source of energy through the following methane-generating redox reaction [4,22]:…”
Section: Potential Originsmentioning
confidence: 99%